Profesionalisme Guru dalam Orientasi Mutu Pendidikan Melalui Pendekatan Masa Depan Siswa - Poliman Padang; Devi Permata Br Bangun; Samuel Sihite; Seevaira Chyta Simanullang; Sri Wahyuni Ayu; Mario Manurung; Jamaludin Rummi (LPPM Politeknik Pratama, 2024)
ofessional teachers are educators who have a thorough understanding of their role and have an awareness of their duties. A deep understanding of the role of professional teachers will help create a learning environment that facilitates students’ creativity in exploring new ideas. The purpose of this study is to find out the professionalism of teachers in orienting the quality of education through a student’s future approach. In this research, a qualitative approach is used with the type of library research. This method involves collecting data by understanding and studying the theories contained in various literatures relevant to the research. Self-Development. As a professional teacher, teachers have an important role in shaping the school as an environment that encourages students’ self-development beyond the routine. Some things that teachers can implement include: 1. Building empathetic relationships, 2. Encouraging independence, 3. Providing constructive or constructive feedback, 4. Inspiring interest in learning, 5. Providing positive behaviors, 6. Integrating holistic learning, 7. Building parental and community involvement.